The Effect of Elderly Gymnastics on Bone Density and Balance in the Elderly at Batara Hati Mulia Foundation - Nurhikmawaty Hasbiah; Aprialiyah Zakiyah Tri S; Andi Rahmaniar Suciani P.; Aco Tang (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
Elderly is the process of slowly disappearing the ability of tissues to repair themselves / replace and maintain their normal structure and function so that they cannot survive the traces (including infection) and repair the damage suffered. Problems that are often experienced by the elderly are decreased bone density and balance problems. In every body activity or movement, the body will always need balance both statically and dynamically so that the position of the human body becomes stable and reduces the risk of falling. This study aims to determine the effect of elderly exercise on bone density and balance in the elderly at the Hati Mulia Foundation, Takalar Regency. This study uses a quasi-experimental research design with a pretest-post-test one group design. The research population is the elderly at the Hati Mulia Foundation, Takalar Regency. The number of samples was 30 people who were divided into 2 groups, namely the control group carried out by the Batara Hati Mulia Gowa Foundation and the control group each 15 people by the Batara Hati Mulia Takalar Foundation. This study used bioelectrical impedance analysis (BIA) to measure bone density and Stork Stand Test to measure balance before and after the Elderly exercise treatment for the treatment group, while the control group was not given any intervention.